Co-ingestion of branched-chain amino acids and carbohydrate stimulates myofibrillar protein synthesis following resistance exercise in trained young men - Jackman, S. R.; Wallis, G. A.; Yu, J.; Philp, A.; Baar, K.; Tipton, K. D.; Witard, O. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2023)
Branched-chain amino acids (BCAA) and carbohydrate (CHO) are commonly recommended postexercise supplements. However, no study has examined the interaction of CHO and BCAA ingestion on myofibrillar protein synthesis (MyoPS) rates following exercise. We aimed to determine the response of MyoPS to the co-ingestion of BCAA and CHO following an acute bout of resistance exercise. Ten resistance-trained young men completed two trials in counterbalanced order, ingesting isocaloric drinks containing either 30.6-g CHO plus 5.6-g BCAA (B + C) or 34.7-g CHO alone following a bout of unilateral, leg resistance exercise. MyoPS was measured postexercise with a primed, constant infusion of L-[ring13C6] phenylalanine and collection of muscle biopsies pre- and 4 hr postdrink ingestion. Blood samples were collected at time points before and after drink ingestion. Serum insulin concentrations increased to a similar extent in both trials (p > .05), peaking at 30 min postdrink ingestion. Plasma leucine (514 ± 34 nmol/L), isoleucine (282 ± 23 nmol/L), and valine (687 ± 33 nmol/L) concentrations peaked at 0.5 hr postdrink in B + C and remained elevated for 3 hr during exercise recovery. MyoPS was ~15% greater (95% confidence interval [-0.002, 0.028], p = .039, Cohen`s d = 0.63) in B + C (0.128%/hr ± 0.011%/hr) than CHO alone (0.115%/hr ± 0.011%/hr) over the 4 hr postexercise period. Co-ingestion of BCAA and CHO augments the acute response of MyoPS to resistance exercise in trained young males.